A forest planting plan for central Kansas - Brock, J. E.; Smith, J. L. (My University, 1908)
Introduction: In 1896 the U.S. Dept. of Forestry submitted to the Experiment Station at the Kansas State Agricultural College, the following plan for a forest planting. The planting was made in accordance with this plan on the old college farm, two miles west of Manhattan, Kansas.
Citation: Brock, J. E. and Smith, J. L. A forest planting plan for central Kansas. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Forests; Kansas; Planting; Forestry; Graduating theses; Senior theses; Theses